(untitled) (Journal of Bangladesh Academy of Sciences, 2022)
This research aimed to assess the concentrations of As, Cd, Cr, Pb, and Zn in Swarna rice (NR) collected from Kaharole, Biral, and Sadar Upazilla of Dinajpur and their reduction by cooking associated submerged fermentation. The levels of As, Cd, Cr, and Zn were lower than the individual metal’s safe limit, but the (Pb) concentrations were found at 0.2582, 0.9028, 0.9164, 0.7303, 0.8574, 0.6440, 0.6622 mg/kg in SR02, SR04, SR05, SR06, SR07, SR08, and SR09 of NR samples, respectively, which were higher than the (Pb) safe limit. Notably, the reduced hazard index (HI) was found from the standard limit 1 for all fermented rice (FR) samples and all boiled rice (BR) samples except SR05. Six different Streptococcus sp. strains were identified in FR that suggested Streptococcal involvement in leaching of HMs during submerged-fermentation. Consequently, compared to NR, hazard index and cumulative carcinogenic risk were declined by several folds in FR. J. Bangladesh Acad. Sci. 46(1); 85-99: June 2022